2000
DOI: 10.1128/aac.44.3.651-653.2000
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inositol Phosphorylceramide Synthase by Aureobasidin A in Candida and Aspergillus Species

Abstract: Inositol phosphorylceramide (IPC) synthase is an enzyme common to fungi and plants that catalyzes the transfer of phosphoinositol from phosphatidylinositol to ceramide to form IPC. The reaction is a key step in fungal sphingolipid biosynthesis and the target of the antibiotics galbonolide A, aureobasidin A, and khafrefungin. As a first step toward understanding the antifungal spectrum of IPC synthase inhibitors, we examined the sensitivity of IPC synthase to aureobasidin A in membrane preparations of Candida s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 15 publications
4
73
0
Order By: Relevance
“…As shown in Fig. 1A, AbA strongly inhibits the growth of filamentous fungi such as A. oryzae, P. oxalicum, and Acremonium sp., previously reported for the yeast Saccharomyces cerevisiae (W303-1A) and other fungi (7)(8)(9)(10)13). However, growth inhibition by AbA was not observed for any Zygomycetes species such as M. hiemalis, R. microsporus, R. pusillus, and A. corymbifera (Fig.…”
Section: Growth Of Fungi Resistant Tomentioning
confidence: 73%
See 1 more Smart Citation
“…As shown in Fig. 1A, AbA strongly inhibits the growth of filamentous fungi such as A. oryzae, P. oxalicum, and Acremonium sp., previously reported for the yeast Saccharomyces cerevisiae (W303-1A) and other fungi (7)(8)(9)(10)13). However, growth inhibition by AbA was not observed for any Zygomycetes species such as M. hiemalis, R. microsporus, R. pusillus, and A. corymbifera (Fig.…”
Section: Growth Of Fungi Resistant Tomentioning
confidence: 73%
“…Aureobasidin A is well known and widely used as an antifungal agent for Eumycetes including yeasts and fungi. It exhibits strong fungicidal activity against many pathogenic fungi, including Candida albicans, Cryptococcus neoformans, and Aspergillus fumigatus (7,8). Recent studies (6) have shown that this antifungal agent inhibits IPC synthase in fungal cells.…”
mentioning
confidence: 99%
“…In contrast to fungi and plants, mammalian cells do not synthesize IPC or GIPCs; instead, choline phosphate is transferred from phosphatidylcholine to the 1-OH group of ceramide, leading to the synthesis of sphingomyelin (SM). This difference in SL metabolism between mammalian cells and fungi represents an attractive target for antifungal drugs such as khafrefungin [15] and aureobasidin A [14,16], which specifically inhibit the IPC synthase.…”
mentioning
confidence: 99%
“…A. pullulans can also produce aureobasidins, polypeptide substances showing fungicidal action, which inhibit the growth of species of the genus Aspergillus (Prasongsuk et al 2013). Aureobasidins are a family of cyclic depsipeptide antibiotics with 18 known derivatives (aureobasidin A to R) that differ in their amino acid composition (Prasongsuk et al 2013;Ikai et al 1991) and are known to inhibit inositol phosphoacrylamide synthase, a key enzyme for fungal sphingolipid synthesis (Zhong et al 2000).…”
Section: Introductionmentioning
confidence: 99%